Case Report: Remarkable and sustained remission of an anaplastic thyroid carcinoma patient to the combined treatment of multimodal radiotherapy, anlotinib and toripalimab - Xing, Yurou; Wu, Xuehu; Li, Zhihui; Wu, Xin (Frontiers in Oncology, 2025)
Anaplastic thyroid carcinoma (ATC) is an infrequent malignant tumor that has a high death rate and a poor prognosis. The therapeutic methods for ATC include traditional surgery, chemoradiotherapy and targeted therapy. However, the effect of ATC treatment is not ideal. We report a patient with ATC who developed rapid local recurrence and multiple systemic metastases after radical thyroidectomy. After multimodal radiotherapy, antiangiogenic therapy and immunotherapy, the patient’s tumors shrunk significantly and achieved long-term control. The therapeutic effect was remarkable. These findings provide a viable new treatment choice for ATC patients in the future.